Vygotsky's Historical-Cultural Approach and professional training in Health Sciences: Vygotsky’s Historical-Cultural Approach and professional training in Health Sciences (La U Investiga, 2021)
Problem: Given the current conditions that humanity is experiencing in the face of the pandemic caused by COVID 19, it is imperative for higher education to orient its substantive functions from innovative and pertinent perspectives to current circumstances. In this sense, the training of Health Sciences professionals requires an epistemological and psychopedagogical conception that allows responding to the current demands of the environments in which it operates. Objective: The present theoretical reflection aims to analyze the main contributions of the Historical-Cultural Approach proposed by Lev Semionovich Vigotsky, as a psychopedagogical foundation for professional training in the area of ​​Health Sciences, in light of building an educational proposal oriented to the fulfillment of the social function of higher education. Methodology: The literature review was developed from the methodological process of MAGG Literature Review sequences by Machi & McEvoy (1). Results: The review discusses the relevance of the postulates of the Cultural Historical Approach, from its epistemological foundation, its conception in the development of thought, learning, teaching, teaching performance and its applicability in professional training in the area of ​​Science health. Conclusion: The theoretical, methodological and practical conceptions of this approach are constituted as intrinsic factors in the construction of an epistemological-psychopedagogical proposal for higher medical education, which contributes towards the cognitive, scientific, personal and social development of the individual.
Keywords: Cultural Historical Approach. Vocational training. Health Sciences.